RESOLUTION DECISION-MAKING TO INCREASE THE ROLE OF THE UNITED NATIONS FOR WORLD PEACE - Edwin Edwin (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
The United Nations (UN) was founded on October 24, 1945 or after World War II ended. At the time of its establishment, the UN consists of 51 member countries and continues to grow until now it has 193 members. The birth of the UN was motivated by the failure of The League of Nations because it could not realize the desire of its founders to create peace throughout the world by preventing war. After World War I, it turned out that World War II was still followed. The UN is considered successful in preventing a widespread war so that until now there has been no World War III. However, in the current situation, wars in several parts of the world have recurred, such as in Syria, Palestine, Azerbaijan and others. The existence of the UN as a universal organization that maintains peace is again being questioned. The ability, especially the Security Council, as one of its organs to prevent war, needs to be improved. Keywords: The Security Council, UN Charter, Veto